PEMANFAATAN OBAT TRADISIONAL UNTUK MENINGKATKAN DAYA TAHAN TUBUH DAN MENCEGAH PENYAKIT COVID 19 - Rofiqoch, Isnaeni; Apriliani, Happy Dwi; Purwati, Purwati (LPPM Institut Pendidikan Nusantara Global, 2022)
Traditional—medicinal plants or herbs are plants that are efficacious to the human body for endurance and treatment. The Covid-19 pandemic in Indonesia has had a huge impact on changes in public health in Indonesia, especially among the people in Banyumas Regency. Improving the body's immunity is needed to prevent the spread of the Covid-19 virus. This is because the spread can be transmitted through coughing droplets (sneezes), therefore if the human immune system is good and the body is in good health this virus will find it difficult to enter the human body. Based on this statement, it is necessary to increase public knowledge about the use of traditional medicines to increase endurance and prevent Covid-19 disease. Based on the results of IBM on the Utilization of Traditional Medicines, it is proven that this activity can increase public knowledge about herbal ingredients that can be used as medicines or concoctions that can increase the human immune system, which is proven by the results of the pre-test with an average value of 57 and After treatment (post-test), it increases to an average of 89.